TURNER’S EVALUATION OF JULIET’S SELF-CATEGORIZATION: A SOCIO-PSYCHOLOGICAL STUDY - Mehak Faiz; Dr Alam Zeb (International Journal of Contemporary Issues in Social Sciences, 2024)
The present study analyses the character of Juliet from Shakespeare's Romeo and Juliet (1965) through the lens of Turner’s Self-categorization Theory, focusing on transformation of her identity. The method of data collection of this research is qualitative method. The study finds that initially, Juliet's personal identity as an obedient daughter aligns with her social identity as a submissive individual of an inferior social group. However, her romantic involvement with Romeo initiates a shift in her personal identity. She develops into a courageous individual determined to control her own fate and her personal identity becomes salient over her social identity. By steadfastly asserting her personal identity, Juliet's actions begin to conflict with the rigid norms dictated by her social group. Moreover, Juliet is unable to undergo the process of depersonalization—where she would conform her personal identity to group norms—plays a critical role in her character development and the tragic events that ensue. Hence, the integration of Turner's Self-categorization in this study provides a deeper understanding of the socio-psychological processes underlying Juliet’s identity conflict.